2020
DOI: 10.3390/plants9030369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spontaneous Haploid Genome Doubling in Maize Breeding

Abstract: Doubled haploid (DH) technology has changed the maize-breeding landscape in recent years. Traditionally, DH production requires the use of chemical doubling agents to induce haploid genome doubling and, subsequently, male fertility. These chemicals can be harmful to humans and the plants themselves, and typically result in a doubling rate of 10%-30%. Spontaneous genome doubling and male fertility of maize haploids, without using chemical doubling agents, have been observed to a limited extent, for nearly 70 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The predictive ability of a given model can be affected by heritability, training population size, the density of the markers, and the mating design alongside with the genetic architecture of the trait (Jumpatong et al 1996). Previous studies and our own data showed that DH-production traits were complex traits controlled by many small-effect QTLs with relatively low heritability (Boerman et al 2020;Ren et al 2020). After comparing multiple GS models, our results suggested rrBLUP and GBLUP (including GBLUP-A and GBLUP-AD) only exhibited subtle differences in predicting the DH-production traits.…”
Section: Genomic Selection Models Performed Equally Well In Predictinmentioning
confidence: 51%
See 1 more Smart Citation
“…The predictive ability of a given model can be affected by heritability, training population size, the density of the markers, and the mating design alongside with the genetic architecture of the trait (Jumpatong et al 1996). Previous studies and our own data showed that DH-production traits were complex traits controlled by many small-effect QTLs with relatively low heritability (Boerman et al 2020;Ren et al 2020). After comparing multiple GS models, our results suggested rrBLUP and GBLUP (including GBLUP-A and GBLUP-AD) only exhibited subtle differences in predicting the DH-production traits.…”
Section: Genomic Selection Models Performed Equally Well In Predictinmentioning
confidence: 51%
“…Chromosome doubling, or the haploid male fertility (HMF) and haploid female fertility (HFF), can be enhanced by chemical reagents, such as colchicine and herbicide (Saisingtong et al 1996), but these chemicals are both harmful for human health and detrimental for the environment. Thus, spontaneous haploid genome doubling has been put on center stage (Ren et al 2017;Boerman et al 2020). Recent QTL studies suggested that the HMF is likely affected by several small effect loci (Ma et al 2018;Ren et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Improving the chromosomal-doubling efficiency in maize haploids can unfold the full potential of DH technology, which could facilitate new selection approaches that are currently not feasible due to the lower efficiency of artificial chromosomal-doubling methods. High chromosomal-doubling efficiency can facilitate phenotypic or marker-assisted selection for simple traits and genomic selection for complex traits at the haploid stage [ 10 ]. This could reduce breeding-cycle time and increase selection intensity and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The overall success rate (OSR) is a criterion that measures success for artificial chromosomal-doubling methods [ 7 ], and the OSR varies from 5 to 35% depending on the protocol and the chemical used [ 6 , 7 , 9 ]. Even though artificial chromosome-doubling methods are extensively practiced in the DH-production pipelines, this process demands considerable manual labor and laboratory and greenhouse facilities, besides employing toxic chemicals [ 2 , 10 ]. Hence, breeding programs are seeking alternative methods that can be operationally simpler, less expensive and not involve toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation